ANALISIS GAYA BAHASA IKLAN KOSMETIKA DAN OBAT-OBATAN BERBAHASA INDONESIA PADA MEDIA MASSA CETAK DI BALI - Candrawati, Ni Luh Komang (Widyadari: Jurnal Pendidikan, 2019)
The article, entitled Analysis of the Language Style of Cosmetics Advertisements and Indonesian Language Drugs in Print Mass Media in Bali, aims to discuss the problem of how the assignment of each sentence in cosmetics advertisements and drugs in Indonesian on the print mass media specifically on commercial advertisements (commercial) , covering what kind of language style is used? In addition, it aims to contribute to the development, preservation and development of the Indonesian language. This paper uses a descriptive qualitative method. Data collection was carried out using the literature review method. Methods and techniques for Presentation of Analysis Results, use formal and informal methods. Based on the analysis results found six kinds of language styles, namely (1) Climax, (2) Repetition, (3) Hyperbole, (4) Personification, (5) Epithet, and (6) Equation or Semile. This paper uses the theory of persuasive functions. The theory of the persuasive function of language is the theory used and it is possible to answer the problem in advertising as a discourse that cannot be separated from its main purpose, namely selling. The main function is predominantly utilized to support the main function of advertising, namely the persuasive function of language as already alluded to implicitly by some advertising researchers (see Hoed, 1992: 5; Leech, 1966: 26; Kasali, 1992: 9; Cook, 1992: 5; Asmah, 1984: 3). In this paper, two views are expressed regarding the theory of language functions, including Jakobson (1963) and Leech (1974). Jacobson's view (1963; in Welaga, 2000: 37-38) stated six kinds of language functions and included persuasive language functions with the term conative function as an expression of the wishes of the speaker directly or immediately carried out by the listener. In this case, language is used to indicate the involvement of the recipient's attention, and also to influence to do what the sender of the message suggests. The conative function is mainly characterized by the use of the pronouns "you" or "you all", and the use of command sentence forms. Noth (1990: 421) in his book Handbook of Semiotics also emphasizes that the six language functions that Jakobson conveys in the communication model are in advertisements. However, the conative function has more roles. Furthermore, it is said that the function of the phatic (phatic) as opening, maintaining relationships or contacts between speakers and listeners and the poetic function (phoetic) as encoding the message is also very prominent in advertising.